Penerapan Metode Drill Untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas IX Materi Statistika di Smp Kristen Rantepao [The Implementation of the Drill Method to Improve Cognitive Learning Outcomes of Grade 9 Students Studying Statistics at a Christian Junior High School in Rantepao] - Astuningtias, Kezia Irene; Appulembang, Oce Datu (JOHME: Journal of Holistic Mathematics Education, 2017)
In mathematics learning, the learning outcomes that are most often measured are the cognitive outcomes because they can be used in evaluating students’ achievement in the things they have learned. This research aimed to see whether the implementation of a drill method can improve the learning outcomes. The method used in this research is Classroom Action Research (CAR) using Kemmis & McTaggart’s model. This research was done in two cycles at a Christian junior high school in Rantepao in October 2016. The subjects were grade 9 students at the school. The instruments used in this research were mentor and peer observations, student’s questionnaire, and tests. The research concluded that the implementation of the drill method improved the cognitive learning outcomes of grade 9 students at the school.ABSTRAK BAHASA INDONESIA: Dalam pelajaran matematika, hasil belajar yang paling sering diukur adalah hasil belajar kognitif karena itu dapat dijadikan bahan evaluasi untuk mengetahui pencapaian siswa akan hal yang sudah dipelajari. Penelitian ini bertujuan untuk melihat apakah penerapan metode drill dapat meningkatkan hasil belajar kognitif siswa. Metode penelitian yang digunakan adalah metode Penelitian Tindakan Kelas (PTK) model Kemmis dan Taggart. Penelitian dilakukan di SMP Kristen Rantepao pada kelas IX pada Oktober 2016 dalam dua siklus. Instrumen yang digunakan yaitu lembar observasi mentor dan teman sejawat, lembar angket siswa, dan tes. Hasil penelitian menyimpulkan bahwa penerapan metode drill dapat meningkatkan hasil belajar kognitif siswa kelas IX materi Statistika di SMP Kristen Rantepao.